Зростання виробництва алюмінієвого лиття на початку XXI століття - Гнатуш, В.А.; Дорошенко, В.С. (Physico-technological Institute of Metals and Alloys, 2023)
The analysis of the global market for aluminum castings in 2000–2017, as well as current trends in production, trade, foundry technologies and foundry alloys are presented. The global market for aluminum alloy castings at the beginning of the XXI century is characterized by dynamism and an increasing trend. Despite the local economic crisis in time, in the period from 2000 to 2017, the production of aluminum castings in the world increased by 2.4 times. The main consumer of such castings is the transport industry (75 % share in 2011), including the automotive industry – 57 %. The countries leading in the production of aluminum castings are China, USA and Japan. Foundry automotive industry uses advanced technologies that are constantly being improved, as evidenced by the examples of castings. Scientists are creating new technologies and foundry alloys with enhanced performance characteristics, such as, for example, Rotocast technology, alloys of the Al-Ce-X system. The expansion of casting technology – Lost Foam casting process with the crystallization of the metal under pressure is known. The outpacing growth in the production of castings from aluminum alloys in the world, with some reduction in the production of castings from iron-carbon alloys, is also confirmed by the topics of research and innovation in the foundry industry, in particular, by the American Foundry Association. Examples are shown of complex construction of aluminum alloy castings for engine building and other body parts, mainly obtained by casting under pressure. A significant range of castings of aluminum alloys has been mastered by Physico-technological Institute of Metals and Alloys of the NAS of Ukraine. Most of these aluminum alloy castings are manufactured according to Lost Foam casting process (LFC process). This technology is successfully developed by the department under the guidance of prof. O.I. Shinsky.